2020
DOI: 10.21203/rs.3.rs-60075/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Utility of a Three Part Differential Hematology Analyzer with CRP for Assessing Malaria

Abstract: BackgroundHematology analyzers display abnormal hematology parameters during malaria infection providing insightful information for suspecting and assessing malaria infection. The goal of this study is to demonstrate the potential of a three part differential hematology analyzer to assess malaria, provide information about the parasitemia, and discuss the importance of combining CRP with hematology parameters to obtain further information about the malaria infection.MethodsThe present study shows the results o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…21 Nishimura et al documented lower TLC and platelet count in malaria and dengue patients with higher MPV, PDW and MCHC. 22 Viswanathan et al has recorded the role of platelet indices in combination with CBC and clinical symptoms can aid in the diagnosis and treatment of tropical acute febrile illnesses. 23 Anabire et al did not find any specific changes in the haematological indices in patients with typhoid fever as compared to malaria patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Nishimura et al documented lower TLC and platelet count in malaria and dengue patients with higher MPV, PDW and MCHC. 22 Viswanathan et al has recorded the role of platelet indices in combination with CBC and clinical symptoms can aid in the diagnosis and treatment of tropical acute febrile illnesses. 23 Anabire et al did not find any specific changes in the haematological indices in patients with typhoid fever as compared to malaria patients.…”
Section: Discussionmentioning
confidence: 99%
“…Motchan et al conducted a 6‐year retrospective analysis of malaria cases and found malaria‐positive cases presents with reduced levels of Hb, RBC count, HCT, TLC, platelet count and PCT whereas RDW, MPV and PDW were elevated significantly paralleled to comparative group 21 . Nishimura et al documented lower TLC and platelet count in malaria and dengue patients with higher MPV, PDW and MCHC 22 . Viswanathan et al has recorded the role of platelet indices in combination with CBC and clinical symptoms can aid in the diagnosis and treatment of tropical acute febrile illnesses 23 .…”
Section: Discussionmentioning
confidence: 99%